Analisis Peningkatan Efektivitas Program Pelatihan Untuk Meningkatkan Kinerja Organisasi Di Kantor Perumda Air Minum Tirta Umbu Kabupaten Nias - Hia, Agustini Mawarni; Fatolosa Hulu, Eliyunus Waruwu, Sukaaro Waruwu, (YUME : Journal of Management, 2025)
This study aims to analyze the effectiveness of training programs in improving organizational performance at the Regional Public Water Company (PERUMDA) Tirta Umbu in Nias Regency. Using the four-level Kirkpatrick evaluation model as the main framework, this study evaluated the reactions, learning, behaviors, and outcomes of the training. The research method used was a descriptive qualitative approach with data triangulation through in-depth interviews, participatory observation, and document analysis. The results showed that the competency-based training program had a positive impact on improving technical skills, operational efficiency, and customer satisfaction. However, there are constraints such as lack of post-training evaluation, low relevance of materials to technical needs, and limited budget and facilities. The study emphasized the importance of managerial support, training needs analysis, and ongoing mentoring to ensure training effectiveness. In conclusion, organization-specific needs-based training can be a key strategy to improve organizational performance and sustainability. The implications of the study include recommendations for improving training policies, improving the quality of facilitators, and optimizing resource support.